The impact of climate change on the most vulnerable women and children in Northern Nigeria: a vulnerability segmentation and geospatial analysis - Michael Kalnoky; Gaspard Pairault; Jessica E Long; Lang Gao; Andrew Buhayar; Daniel Helldén (Environmental Research: Health, 2026)
Abstract Women and children in Northern Nigeria face increasing climate-related hazards and persistent health challenges. However, the relationship between climate-related environmental exposure and vulnerability to poor reproductive, maternal, neonatal, and child health (RMNCH) outcomes remains poorly understood. We applied a vulnerability-segmentation approach to categorize women aged 15–49 yr ( n = 19041) in the 2018 Nigeria demographic and health survey into segments experiencing different levels of vulnerability to poor RMNCH outcomes. Using descriptive geospatial analysis, we overlaid measures of extreme heat exposure (maximum wet-bulb globe temperature), drought conditions (soil moisture levels), and food availability (normalized difference vegetation index) to examine how climate change vary across these vulnerability segments. Eleven distinct segments with unique vulnerabilities to RMNCH outcomes were identified. Across all climate-change indicators, segments at the highest risk of poor RMNCH outcomes were also more exposed to climate-related hazards compared with lower-risk segments. This pattern was particularly pronounced in rural areas. Overall, the most vulnerable women and children in Northern Nigeria experience high and overlapping levels of climate-change exposure. Targeted and context-specific climate-adaptation strategies, both within and beyond RMNCH programs, are essential to address the disproportionate burden faced by these high-risk groups.